Impact of Cytomegalovirus on Long-term Mortality and Cancer Risk After Organ Transplantation. Issue 9 (September 2015) - Desai, Rajeev; Collett, Dave; Watson, Christopher J. E.; Johnson, Philip J.; Moss, Paul; Neuberger, James
Abstract : Background: There is conflicting evidence of the effect of cytomegalovirus (CMV) infection on survival and the risk of cancer after transplantation. Methods: All recipients of kidney, liver, heart, and lung transplants in the United Kingdom between 1987 and 2007 with known CMV immunoglobulin G status were identified from the U.K. Transplant Registry. Based on the donor-recipient CMV status, recipients were grouped into: donor (D) negative recipient (R) negative (D− R−), D−R+, D + R+ and D + R−. Cancer data were obtained from the Office for National Statistics. The impact of CMV infection on survival and cancer incidence was assessed. Results: The 10-year posttransplant survival in D−R− recipients (73.6% [95%CI, 72.3, 74.9]) was significantly higher ( P < 0.0001) than in other recipients (66.1% [65.3, 66.9]). Compared with the D− R− group, the risk-adjusted hazard of death within 10 years of transplantation for D+ R− group was 14% higher for kidney recipients ( P = 0.0495), 13% higher for liver recipients ( P = 0.16), 34% higher for heart recipients ( P = 0.01), and 35% higher for lung recipients ( P = 0.006). The proportion of recipients with a cardiovascular cause of death was higher ( P = 0.03) among the recipients exposed to CMV (18%) as compared to the D− R− recipients (16%). The CMV status was not associated with an increased risk of cancer. Conclusions: The results from this large study demonstrate that CMV is associated with a significantly increased long-term mortality in kidney and cardiothoracic transplant recipients and an increased risk of cardiovascular death but not of posttransplant cancer. Abstract : A large registry study from the United Kingdom covering all kidney, liver, heart and lung recipients over a 20-year period shows the highly significant contribution of CMV status to recipient survival, with the high risk groups having substantial increases in overall and cardiovascular but not cancer-related mortality. Supplemental digital content is available in the text.